Global Diplomacy in The Face of Crisis: International Responses on Covid 19 Pandemic - Novianti Adistia, Margaretha (Riviera Publishing, 2023)
The COVID-19 pandemic has significantly impacted nations worldwide, requiring a coordinated international response beyond diplomatic boundaries. The pandemic has led to significant changes, such as reduced travel and eco-friendly transportation, increased government intervention, and radical policy shifts like universal basic income and Green New Deal initiatives. The pandemic has also highlighted the importance of evidence-based decision-making and the risks of disregarding scientific expertise, influencing populist and authoritarian movements. The pandemic presents an opportunity for transformative policy changes, with behavioral changes such as reduced travel and eco-friendly infrastructure promoting sustainable mobility and climate change. However, the crisis also challenges the international order, with rising powers and traditional supporters. Urgent reform is needed to strengthen crisis surveillance, prevention, and response. Political scientists play a crucial role in guiding policymakers, but barriers like slow publication processes and divides between scholars and policymakers hinder the effective translation of research into action. Understanding and analyzing the international response is vital for combating the pandemic effectively. This article uses qualitative and literature review research methods. Qualitative research addresses questions about understanding the meaning and experience dimensions of humans' lives and social worlds. COVID-19, also known as the coronavirus disease 2019, has emerged as a significant global challenge and tragedy, rapidly spreading worldwide. In conclusion, the COVID-19 pandemic has been a significant global challenge with far-reaching consequences on various aspects of society.